Postmoderne epistemologie en postkoloniale hermeneutiek - Aarde, Andries van (HTS teologiese studies, 2004)
Postmodern epistemology and postcolonial hermeneuticsPostcolonial hermeneutics is concerned with linguistic, cultural and geographical transfer. Within the framework of biblical studies it explores strategies of interpreting texts from the situation of previously colonised people who are accommodated in a new liberated context, but find themselves both included and excluded. Biblical texts are historically considered to be both the products of people who were subjected to the exploitation of Middle-Eastern and Graeco-Roman super powers and interpreted today in the third world by people who also were subjects of modern colonial powers. Postcolonial studies represent a postmodern epistemology which implies a deconstructive approach to hermeneutics. The article consists of five “preludes”, introducing postmodern epistemology, postcolonial hermeneutics, postcolonial biblical studies, and unlocking potential biblical research in South Africa.